Lexical Cohesion Analysis of Will Smith’s Full Interview with Ellen - Sagala, Juni Arta; Mubarak, Zia Hisni (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study's objective is to determine the types of lexical cohesion employed in "Will Smith's Full Interview with Ellen" based on Haliday & Hasan (1976) lexical cohesion theory. This study employs a qualitative methodology that focuses on repetition, synonym, antonym, meronym, and hyponym types of lexical cohesion. Data were gathered by the researcher through observation and note-taking methods. The "Will Smith's Full Interview with Ellen" contains all the lexical cohesion types that were the subject of this investigation. The researcher discovered nine repetitions, three synonyms, two antonyms, and one hyponym. It follows that Repetition exhibits the highest level of lexical cohesion throughout "Will Smith's Full Interview with Ellen".” The speaker tends to repeat words, phrases, or sentences, which the researcher discovered from the data that has been evaluated.  The conclusion from the concept of lexical cohesion is that the use of lexically or semantically related words in a text has a positive impact on the connectedness, fluency, and clarity of communication. Lexical cohesion helps build strong connections between parts of the text, ensures a consistent flow of thought, and improves reader comprehension.